Black sexualities : probing powers, passions, practices, and policies - Battle, Juan, 1968-; Barnes, Sandra L. (New Brunswick, N.J. : Rutgers University Press, 2010)
Contains twenty articles in which various authors explore issues in the field of Black sexualities, covering identity theories and frameworks; descriptions, depictions, and responses; citizenship, activism, and legal dynamics; systemic and personal stresses; and the life course.
Nontraditional, nonconforming, and transgressive gender expression and relationship modalities in black communities / Layli Phillips, Marla R. Stewart -- Creation out of bounds: toward holistic identity / E. Christi Cunningham -- On the fear of small numbers: a twenty-first-century prolegomenon of the U.S. Black transgender experience / Enoch H. Page, Matt U. Richardson -- Blackness, sexuality, and transnational desire : initial notes toward a new research agenda / Jafari S. Allen -- Pathologizing black sexuality : the U.S. experience / Kevin McGruder -- Dangerous profiling : recent media representations of black male sexuality / Ruby Tapia, Jeffrey McCune, Jennifer Devere Brody -- Revisiting black sexualities in families : problems, puzzles, and prospects / Erica Chito Childs, Stephanie Laudone, Latoya Tavernier -- To be fluent in each other's narratives : surplus populations and queer of color activism / Roderick A. Ferguson -- Prison, crime, and sexual health in the United States : how the criminal justice systems contribute to health disparities in the black community / Torrance Stephens -- Black sexual citizenship : understanding the impact of political issues on those at the margins of race, sexuality, gender, and class / Sean Cahill -- Racialized justice spreads HIV/AIDS among blacks / Anthony J. Lemelle -- Black and Latino same-sex couple households and the racial dynamics of antigay activism / Sean Cahill -- Blacks and racial appraisals : gender, race, and intraracial rape / C. Shawn McGuffey -- When secrets hurt: HIV disclosure and the stress paradigm / Robert Peterson -- Black female sex workers : racial identity, black feminist consciousness, and acculturated stress / Stephanie L. Tatum -- Yes, Jesus loves me : the liberating power of spiritual acceptance for black lesbian, gay, bisexual, and transgender Christians / Tonyia M. Rawls -- Black mother-daughter narratives about sexuality : the influence of black religious symbolism on attitudes and behavior / Sandra L. Barnes, Mia Smith Bynum -- Black youth sexuality : established paradigms and new approaches / Marcus Anthony Hunter, Marissa Guerrero, Cathy J. Cohen -- "I'll be forever mackin'" : the social construction of black masculine identity in hip hop's platinum age / Jonathan W. Gray -- Black senior women and sexuality / Bette J. Dickerson, Nicole Rousseau -- Epilogue: What's next for the study and application of black sexualities?
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: African Americans -- Social conditions; African Americans -- Sexual behavior; Sex customs -- United States; Noirs américains -- Conditions sociales; Noirs américains -- Sexualité.; Vie sexuelle -- États-Unis.; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; SOCIAL SCIENCE -- Sociology -- General; African Americans -- Sexual behavior; African Americans -- Social conditions; Sex customs; United States; Sexual practices